Adoption analysis of resource-conserving technologies in rice (Oryza sativa)–wheat (Triticum aestivum) cropping system of South Asia - SINGH, RAM; OLAF, ERENSTEIN; SAHARAWAT, YASHPAL SINGH; CHAUDHARY, NEELAM; JAT, M L (The Indian Journal of Agricultural Sciences, 2012)
The bread and rice baskets of South Asia feeding 20% of world population are showing stalled production due to fatigued natural resource bases. The present survey assesses the constraints in adoption of integrated crop and resource management practices in rice (Oryza Sativa L.) wheat (Triticum aestivum L. emend. Fiori & Paol.) systems of Indo- Gangetic plains. The research and developmental activities have a positive impact on resource-conserving technology (RCT) explain first then use RCT use rates. Further, study confirmed that RCTs generally are cost reducing without yield loss, thereby enhancing farmers’ income. The village surveys do however, highlight that the better endowed farmers tend to be the first adopters of RCTs. Purposive efforts are therefore needed to ensure that access to and uptake of RCTs is more inclusive. The marked regional variation also emphasizes the need for local adaptation – giving further impetus to the need for on-farm R and D initiatives to help adapt promising technological innovations to the local and diverse circumstances faced by resource poor farmers.